In Search For New Manifesto - Bratina, Boris R.; Bratina, Oksana A. (Sociološki pregled, 2018)
In this paper authors present the new diagnosis of the contemporary “state of aﬀairs”. To be precise, they look for the emancipation possibilities, bearing in mind the history of class-liberation struggle. Teir main thesis, gradually shaped through the text, is the insight that the class struggle has moved from state to global level. In other words, the authors maintain that accents and conditions of the class struggle have moved from national to global scale, and today the same class struggle predominantly takes place between proletarian nations and bourgeois nations. The authors emphasize causes of such disposition, and discuss consequences and strategies of such struggle under ultimate circumstances. Keywords: The Manifesto of the Communist Party, revolution, capitalism, proletarian nations, bourgeois nations, racism.